Аналіз електромагнітної сумісності мереж LTE з різними видами дуплексу - Панченко, Р. С.; Білик, В. О. (ХНУРЕ, 2019)
In the report are shown mechanisms of mutual interfering influence of the LTE networks with the mixed types of duplex FDD and TDD. The special attention is paid to influence of not synchronized LTE-TDD networks, and also the LTE-TDD and LTE-FDD networks. In the report the methodology of an assessment of conditions of electromagnetic compatibility of such LTE networks, based on the accounting of the specified probabilities is considered, results of statistical modeling on the basis of which concrete practical recommendations for operators of networks of cellular communication are formulated are given.
Keywords: LTE; TDD; ЕМС; FDD